2011
DOI: 10.1038/bmt.2010.327
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia and its association with enhanced stem cell mobilization and harvest after high-dose cyclophosphamide+G-CSF

Abstract: High-dose chemotherapy with autologous peripheral blood SCT is a common treatment option in several hematological and non-hematological malignancies. So far, prediction of successful stem cell mobilization and harvest is limited. Just recently, hypercholesterolemia was shown to increase mobilization of hematopoietic progenitor cells into the peripheral circulation in mice. On the basis of these results, we performed a retrospective multivariate analysis incorporating a variety of clinical parameters in 83 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…[3][4][5] Moreover, hypercholesterolemia, which frequently accompanies increased BMI, seems to promote stem-cell mobilization, and this was documented in both an experimental murine model, and a retrospective analysis of clinical data. 6,7 High cholesterol levels may interfere with the SDF-1/CXCR4 axis by induction of a proinflammatory state, activation of complement the cascade and an increase in serum SDF-1. Plerixafor is a new agent used in combination with G-CSF in myeloma and lymphoma patients, who failed a previous mobilization attempt.…”
mentioning
confidence: 99%
“…[3][4][5] Moreover, hypercholesterolemia, which frequently accompanies increased BMI, seems to promote stem-cell mobilization, and this was documented in both an experimental murine model, and a retrospective analysis of clinical data. 6,7 High cholesterol levels may interfere with the SDF-1/CXCR4 axis by induction of a proinflammatory state, activation of complement the cascade and an increase in serum SDF-1. Plerixafor is a new agent used in combination with G-CSF in myeloma and lymphoma patients, who failed a previous mobilization attempt.…”
mentioning
confidence: 99%
“…Nonetheless, it is possible that in addition to regulating ERα function, 27HC also influences HSCs through effects on bile acid biosynthesis. Our results offer a potential explanation for the long-standing observation that increased cholesterol levels are associated with increased HSPC mobilization in mice and humans (11)(12)(13)(14)(15)(16). 27HC levels increase as cholesterol levels increase (6).…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have reported a correlation between cholesterol levels and HSPC numbers in human blood (34). Patients with hypercholesterolemia mobilize larger numbers of CD34 + HSPCs following treatment with cyclophosphamide and G-CSF as compared with patients with lower cholesterol levels (14). Moreover, plasma cholesterol levels increase in humans during pregnancy (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In our study, patients were classified by clinical diagnosis, not confirmed by laboratory values. This allowed us to examine the impact of hyperlipidemia and its long-term sequelae on mobilization but did not, if the patient is appropriately treated, allow us to examine the impact of elevated blood lipids.…”
mentioning
confidence: 99%